2018
DOI: 10.1016/j.mib.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Rational engineering of synthetic microbial systems: from single cells to consortia

Abstract: One promise of synthetic biology is to provide solutions for biomedical and industrial problems by rational design of added functionality in living systems. Microbes are at the forefront of this biological engineering endeavor due to their general ease of handling and their relevance in many potential applications from fermentation to therapeutics. In recent years, the field has witnessed an explosion of novel regulatory tools, from synthetic orthogonal transcription factors to posttranslational mechanisms for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 91 publications
2
60
0
Order By: Relevance
“…In conclusion, we have successfully implemented ECF σ factor-based autonomous timers in vivo and demonstrated that the concept is generally applicable to different ECF groups, organisms or genetic systems. In the future we expect that the combination of orthogonal ECF σ factors with other tools for transcriptional, translational and post-translational synthetic circuit design ( 55 ) will greatly facilitate the development of more sophisticated in vivo gene expression programs in a variety of biotechnological applications and production hosts.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have successfully implemented ECF σ factor-based autonomous timers in vivo and demonstrated that the concept is generally applicable to different ECF groups, organisms or genetic systems. In the future we expect that the combination of orthogonal ECF σ factors with other tools for transcriptional, translational and post-translational synthetic circuit design ( 55 ) will greatly facilitate the development of more sophisticated in vivo gene expression programs in a variety of biotechnological applications and production hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Though commonly employed in bioreactor and cellular interaction studies, the limitations of liquid culture systems are especially poignant when attempting to control the dynamics of a multi-organism consortium. Specifically, repeated (and sometimes even single) batch liquid co-cultures typically fail over time without sophisticated genetic control systems or particular nutrient conditions that seek to minimize the competitive growth bias that often occurs when utilizing disparate microorganisms [8][9][10][11] .…”
mentioning
confidence: 99%
“…A trade-off was found between robustness to environmental disturbances and robustness to perturbations in available resources for the genetic circuit 41 . Synthetic microbial consortia have been used for engineering multicellular synthetic systems [42][43][44] and metabolic pathways 45 .…”
Section: Resource Competition Is Commonplace At Various Levels Of Regmentioning
confidence: 99%